2018
DOI: 10.1002/pon.4917
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of psychiatric diagnoses to extent of opioid prescription in the first year post‐head and neck cancer diagnosis: A longitudinal study

Abstract: Purpose The purpose of this study was to determine, within the first‐year post–head and neck cancer (HNC) diagnosis, the contribution of past and upon HNC psychiatric diagnoses (ie, substance use disorder, major depressive disorder, and anxiety disorder) to the extent (ie, cumulated dose) of opioid prescription. Methods Prospective longitudinal study of 223 consecutive adults (on 313 approached; 72% participation) newly diagnosed (<2 weeks) with a first occurrence of primary HNC, including Structured Clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
1
9
1
Order By: Relevance
“…In the United States, three out of four patients with cancer receive opioids for cancer pain management [1,2]. In patients with head and neck cancers, opioids are frequently prescribed (55.5-83.1%) in the early phases of oncological treatments, and in 39.3% they are given in high dosages [3,4]. This evidence supports previous studies indicating that patients with head and neck cancers have greater odds of receiving opioids during their cancer treatment [5][6][7].…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…In the United States, three out of four patients with cancer receive opioids for cancer pain management [1,2]. In patients with head and neck cancers, opioids are frequently prescribed (55.5-83.1%) in the early phases of oncological treatments, and in 39.3% they are given in high dosages [3,4]. This evidence supports previous studies indicating that patients with head and neck cancers have greater odds of receiving opioids during their cancer treatment [5][6][7].…”
Section: Introductionsupporting
confidence: 77%
“…This entity is defined as the use of opioids between 90 to 180 days after surgery and in a large cohort of mixed cancer patients; its rate ranged from 4.5% to 58.9% [12]. The unintended consequences of persistent opioid use include tolerance, misuse, and lower levels of quality of life [4]. Therefore, it has been suggested that the understanding of the patterns of opioid use after surgery should be one of the initial steps to avoid persistent opioid use, misuse, and diversion [13].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, these efforts should be integrated into primary care and school‐based health clinics because, as survivors become further from treatment, they may not see oncology specialists as frequently. Additional efforts may include integrating behavioral health services and substance abuse specialists into survivor care for AYA patients 28,37 …”
Section: Discussionmentioning
confidence: 99%
“…We selected these cancers to represent common cancers (breast, colorectal, and lung), cancers with significant long-term survival (breast, colorectal, and head and neck), cancers with alcohol and tobacco as predominant risk factors (lung, head and neck, and colorectal), cancers that might be treated with multimodality therapy (including hormone therapy for breast and prostate cancers and targeted and immune therapies for lung cancer), and cancers with a high burden of posttreatment pain (lung and head and neck). [35][36][37][38][39][40][41][42][43][44][45][46][47] To minimize the inclusion of LTOT episodes prescribed during cancer treatment or at the end of life, follow-up began 1 year after diagnosis and was censored at hospice entry, a second cancer diagnosis, 6 months before death, or the end of 2016. Survivors were excluded if they did not have continuous coverage through Medicare Parts A, B, and D from 1 year before the diagnosis through the end of follow-up.…”
Section: Data Source and Cohortmentioning
confidence: 99%